Literature, geography, and the postmodern poetics of place - Prieto, Eric, 1966- (New York : Palgrave Macmillan, 2013)
"Eric Prieto is a professor of French and Comparative Literature at the University of California, Santa Barbara. He is the author of Listening In: Music, Mind, and the Modernist Narrative, and numerous essays on music-and-literature, literary spatiality, Caribbean literature, and literary theory"--
"This book opens up an understudied area within the field of literary spatiality: the question of geographical emergence. A study of contemporary literary representations of place, it draws on phenomenological, poststructural, and postcolonial theories of space and place to show how literature contributes to the formation of new geographical identities. With chapters devoted to the in-between spaces of Samuel Beckett, France's suburban ghettoes, and the postcolonial proto-nations of France's Caribbean territories, this study emphasizes literature's ability to subtly but decisively shape readers' attitudes toward the world around them, making it possible to see such places not as defective or derivative versions of established modes of dwelling but as laboratories for the ways of life of tomorrow"--
Table Of Contents: t t t Index
Includes bibliographical references and index
Keywords: Place (Philosophy) in literature; Literature -- 20th century -- History and criticism; Literature -- 21st century -- History and criticism; Liminality in literature; Postmodernism (Literature)